2014
DOI: 10.1007/s00784-013-1184-z
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with black tooth stain in Chinese preschool children

Abstract: In clinics, dentists should pay more attention to this aesthetic problem for the relative high prevalence of black tooth stain in primary dentition. Also, the related factors can be explained to parents for the prevention of black tooth stain in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
65
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(78 citation statements)
references
References 19 publications
9
65
3
1
Order By: Relevance
“…These different prevalence values may be caused by the differences in eating/oral hygiene habits, related oral microbiological differences and also population sampling methods employed in these studies (4). Black stain prevalence was not different among boys and girls in our study, in agreement with previous studies (18,24,26).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These different prevalence values may be caused by the differences in eating/oral hygiene habits, related oral microbiological differences and also population sampling methods employed in these studies (4). Black stain prevalence was not different among boys and girls in our study, in agreement with previous studies (18,24,26).…”
Section: Discussionsupporting
confidence: 93%
“…Black stain occurrence has been associated with lower risk for caries in preschoolers by França-Pinto et al (19), Boka et al (25) and Chen et al (26). Bhat (22) reported lower caries experience in 7-11 year olds and Sutcliffe (24)[in 11-13 year olds with black stain.…”
Section: Discussionmentioning
confidence: 94%
“…This finding corroborates the findings of a previous population-based study wherein black stains were associated with lower dental caries occurrence in primary dentition, when adjusting for social, demographic and behavioral factors 12,14 . Other non-populational studies found this association in permanent dentition 9,10 .…”
Section: Discussionsupporting
confidence: 91%
“…França-Pinto el al. 14 detected a higher frequency of black stains in children from lower socioeconomic backgrounds, and Chen et al 12 found the association with birthplace, parents' educational level, intake frequency of soy sauce and use of nursing bottle. 9 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation